Evaluating the impact of enterprise education competitions upon entrepreneurial intentions of STEMM women early career researchers - Achtzehn, Sahattaya (2023)
This thesis explores whether an enterprise education competition (EEC), promoted as best practice vehicle of entrepreneurial education (EE), may have gendered outcomes in terms of differential impacts upon women participants, given mixed findings relating to the efficacy of EE for women which is considered to relate to the acknowledged masculine construction of entrepreneurship. Thus, this thesis investigates the influence of an EEC on the entrepreneurial self-efficacy (ESE), entrepreneurial intentions (EI) and perceived gender barriers to entrepreneurship of STEMM women early career researchers (ECRs). Of novelty, the theoretical framework draws upon Social Cognitive Career Theory (SCCT), from the career literature, which captures the socio-economic influences of perceived gender barriers upon entrepreneurial career intentions, while also exploring the predispositions of men and women EEC participants.